2012
DOI: 10.3389/fpsyt.2012.00078
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Modulates Human Color Discrimination in a Pathway-Specific Manner

Abstract: Previous research showed that transcranial direct current stimulation (tDCS) can modulate visual cortex excitability. However, there is no experiment on the effects of tDCS on color perception to date. The present study aimed to investigate the effects of tDCS on color discrimination tasks. Fifteen healthy subjects (mean age of 25.6 ± 4.4 years) were tested with Cambridge Color Test 2.0 (Trivector and ellipses protocols) and a Forced-choice Spatial Color Contrast Sensitivity task (vertical red-green sinusoidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…As the neural correlates of many visual functions are better known than the ones underlying higher order cognitive functions or the ones underlying most (or all) other senses, visual perception research has also helped us to understand how specific tDCS effects are. This can be seen in the early investigations by Antal et al (2001Antal et al ( , 2003bAntal et al ( , 2004a and in the more recent works showing a high functional specificity of tDCS (Costa et al, 2012(Costa et al, , 2015a. In what concerns clinical research, works like Plow et al (2011Plow et al ( , 2012a and Sunwoo et al (2013), have shown that tDCS can be effectively used in post-stroke rehabilitation of a sensory function (as until recently we only knew cases of tDCS use in post-stroke rehabilitation of motor functions).…”
Section: Visualmentioning
confidence: 97%
See 4 more Smart Citations
“…As the neural correlates of many visual functions are better known than the ones underlying higher order cognitive functions or the ones underlying most (or all) other senses, visual perception research has also helped us to understand how specific tDCS effects are. This can be seen in the early investigations by Antal et al (2001Antal et al ( , 2003bAntal et al ( , 2004a and in the more recent works showing a high functional specificity of tDCS (Costa et al, 2012(Costa et al, , 2015a. In what concerns clinical research, works like Plow et al (2011Plow et al ( , 2012a and Sunwoo et al (2013), have shown that tDCS can be effectively used in post-stroke rehabilitation of a sensory function (as until recently we only knew cases of tDCS use in post-stroke rehabilitation of motor functions).…”
Section: Visualmentioning
confidence: 97%
“…In fact, there is some psychophysical evidence supporting this interpretation. First, many studies show changes in thresholds (e.g., Antal et al, 2003a;Grundmann et al, 2011;Costa et al, 2012Costa et al, , 2015a. Some studies have also analyzed tDCS outcomes using a signal detection theory approach.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 3 more Smart Citations